Meta-analysis: The Effectiveness of Physics Learning Media on Students' Creative Thinking Abilities - Nur Aulyatun Hasanah; Ai Nurlaela; Fuji Hernawati Kusumah (Journal of General Education and Humanities, 2026)
Indonesian students’ creative thinking achievement remains low (PISA 2022: 19/60; 31% reached baseline proficiency), indicating an urgent need for effective physics learning media. This meta-analysis aimed to determine the overall effectiveness of physics learning media in improving students’ creative thinking skills and to compare effects by media type and education level. Following PRISMA guidelines, we systematically searched and screened quantitative quasi-experimental studies published in 2017–2025, yielding 10 eligible articles, and calculated effect sizes using Cohen’s   to synthesise results. The findings showed a high overall effect of physics learning media on creative thinking (mean ES = 1.06), with moving audio-visual/interactive media producing the highest mean effect (ES = 1.33) and stronger effects in senior high school than junior high school (ES = 1.15 vs. 0.69). These results indicate that interactive and technology-supported physics media are effective for strengthening students’ creative thinking and should be prioritised in classroom practice.